Exercise training induces benign right ventricular hypertrophy along with functional improvement and without pathological processes or arrhythmogenicity in a rodent model of athletes heart. (14th October 2021) - Olah, A; Bodi, B; Sayour, A A; Ruppert, M; Barta, B A; Virag-Tulassay, E; Bottlik, O; Papp, Z; Merkely, B; Radovits, T
Abstract: Introduction: Regular sport activity leads to the adaptation of cardiac structure and function, the so-called athlete's heart. Research projects over the last years have focused on exercise-induced adaptation of the right ventricle (RV), because the disproportionate load on the RV - when compared with the left ventricle - might lead to pathological consequences, such as myocardial interstital fibrosis or chamber dilation. Purpose: We aimed at investigating comprehensively RV alterations induced by regular aerobic exercise training in a rat model of athlete's heart. Methods: Young, adult rats were divided into control (Co) and exercised (Ex) groups (n=12–12). Exercised rats underwent a 12-week-long swim training program. In vivo electrophysiological study and in vitro cellular force assessments on isolated cardiomyocytes were carried out to investigate electrical and functional RV alterations, respectively. Molecular biological (qRT-PCR, Western-blot) and histological investigations were applied to reveal underlying mechanisms. Results: Exercise training was associated with increased RV cardiomyocyte diameter (12.5±0.1 μm Co vs. 13.8±0.2 μm Ex, p<0.05), that was associated with hyperphosphorylation of protein kinase B (Akt). RV cardiomyocytes from exercised animals showed improved calcium sensitivity and increased maximal force development, that was associated with hypophosphorylation of troponin I. We found increased length of repolarization as reflected by prolonged QT interval and ventricular effective refracter period (VERP: 44.0±1.6 ms Co vs. 52.8±2.1 ms Ex, p<0.05) along with decreased gene expression of potassium channels (Kcnd2, Kcnj2). We could not induce ventricular arrhythmia by programmed stimulation. Picrosirius staining did not reveal fibrosis, that was associated with unchanged protein expression of connective tissue growth factor (CTGF) and gene expression of profibrotic markers (such as TGF-β). Gene expression of apoptotic markers (Bax, Bcl-2) and fetal gene program (such as β-MHC) did not differ between groups. Conclusions: According to our data, regular swim training induced RV hypertrophy, that was associated with functional improvement (improved calcium sensitivity and maximal force), hypophosphorylation of troponin I and prolonged repolarization without characteristic pathological alterations or arrhythmogenicity of RV myocardial tissue. FUNDunding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): National Research, Development and Innovation Office of Hungary